Kajian Efektivitas Mediasi untuk Mencegah Perceraian: Study of the Effectiveness of Mediation to Prevent Divorce - Ngismatul Choiriyah; Achmadi Achmadi (​Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2026)
The rising divorce rate in Indonesia demands optimizing the role of mediation in court as a non-litigation effort to reconcile the parties. Mediation is a mandatory procedure under Supreme Court Regulation (PERMA) No. 1 of 2016, but its success in preventing divorce remains fluctuating. This article examines the effectiveness of mediation in mitigating domestic conflict and identifies factors that hinder the success of the peace process in court. This research uses a normative-empirical method with a sociological-legal approach, drawing on literature and case statistics. The results of the study indicate that the mediator's competence strongly influences mediation effectiveness, the parties' good faith, and the duration of the mediation process. Although procedurally implemented, mediation often becomes merely an administrative formality because the parties' firm desire for divorce has already hardened. Therefore, strengthening the role of professional mediators and adopting a deeper psychological-religious approach are needed to increase the success rate of peace settlements substantially.